Understanding online health information seeking behavior of older adults: A social cognitive perspective - Ma, Xiumei; Liu, Yunxing; Zhang, Pengfei; Qi, Rongtao; Meng, Fanbo (Frontiers in Public Health, 2023)
Online health information seeking has been verified to play a crucial role in improving public health and has received close scholarly attention. However, the seeking behavior of older adults, especially the underlying mechanism through which they are motivated to seek health information online, remains unclear. Furthermore, compared to young people, it is more necessary to understand how to promote online health information seeking of old adults due to their high demand for health information and low IT competence. Consequently, this study addresses the issue by proposing a theoretical model leveraging social cognitive theory. Specifically, we identified IT self-efficacy and IT innovativeness as personal factors and professional support and social support as environmental factors. Based on the responses to a survey that included 347 older people in China, this study demonstrates that IT self-efficacy and IT innovativeness facilitate older adults to seek health information online by increasing their perceived benefit of using the internet. Additionally, professional support and social support enhanced older adults’ online seeking behavior by promoting their health awareness. We also found that perceived benefit displayed a stronger impact than health awareness on older adults’ behavior related to searching for health information online. The discussion concludes by presenting the study’s implications and limitations, along with suggestions for future research.